2018
DOI: 10.3390/cryst8040152
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Transition of ZnO Nanorod Arrays Synthesized by a Two-Step Aqueous Solution Method

Abstract: ZnO nanorod arrays (ZNAs) with vertically-aligned orientation were obtained by a two-step aqueous solution method. The morphology of the ZnO nanorods was regulated by changing the precursor concentration and the growth time of each step. ZnO nanorods with distinct structures, including flat top, cone top, syringe shape, and nail shape, were obtained. Moreover, based on the X-ray diffraction (XRD) and the transmission electron microscope (TEM) analysis, the possible growth mechanisms of different ZnO nanostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The dehydration of [Zn(OH)4] 2− in the final stage takes place by heating the solution to a mild temperature to generate ZnO (reaction 3) [88,94]. The chemical reactions involved for the zincate formation and its subsequent dehydration to produce ZnO are given by [88,93]: [79] under the terms of the Creative Commons Attribution 3.0 license.…”
Section: Crystal Growth Unit (Zincate)mentioning
confidence: 99%
See 1 more Smart Citation
“…The dehydration of [Zn(OH)4] 2− in the final stage takes place by heating the solution to a mild temperature to generate ZnO (reaction 3) [88,94]. The chemical reactions involved for the zincate formation and its subsequent dehydration to produce ZnO are given by [88,93]: [79] under the terms of the Creative Commons Attribution 3.0 license.…”
Section: Crystal Growth Unit (Zincate)mentioning
confidence: 99%
“…A basic solution with water/organic compound as the solvent used in dissolving metal salt precursor. The zinc salts generally employed include zinc nitrate (Zn(NO 3 ) 2 ), zinc chloride (ZnCl 2 ), zinc sulfate (ZnSO 4 ) and zinc acetate dihydrate (Zn(CH 3 COO) 2 • 2H 2 O) [88][89][90][91][92][93]. In a typical synthesis, the dissolution of zinc salt in a solvent gives Zn 2+ ions that react with hydroxyl group to form Zn(OH) 2 (reaction 1).…”
Section: Crystal Growth Unit (Zincate)mentioning
confidence: 99%
“…Co-precipitation method involves the dissolution of a metal salt precursor in water/organic solvent for precipitating oxo-hydroxide in the presence of a strong alkali metal hydroxide (MOH; M = Li, Na, K, Cs), or weak hexamethylenetetramine (HMTA) [210][211][212][213][214]. In the process, zinc metal salt precursor decomposes in the solution to yield Zn 2+ for forming Zn(OH) 2 .…”
Section: Co-precipitation Methodsmentioning
confidence: 99%
“…The [Zn(NH 3 ) 4 ] 2+ complex also acts as the growth unit for ZnO nuclei. Overall, the reactions are given as follows [210,211],…”
Section: Co-precipitation Methodsmentioning
confidence: 99%
“…At present, microwave absorbing materials with lightweight electromagnetic are widely used in people’s livelihoods and military needs, and its property enhancement has also become a hot spot of domestic and international research [1,2,3,4,5]. Previous studies have found that the intrinsic electromagnetic wave absorption mechanisms of traditional single-phase ferrite [6], magnetic metal [7], C-type absorbing [8], semiconductor [9] and macromolecule absorbing materials [10] are mainly their own single dielectric loss and magnetic loss, which can no longer meet the need for an excellent absorbing property.…”
Section: Introductionmentioning
confidence: 99%